Prevalência e fatores associados à depressão em estudantes de medicina da Universidade Federal do Amapá - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2016)
The medical school graduation presents several stressors that can trigger psychiatric disorders. This research aims to determine the prevalence and factors associated with depressive symptoms in medical students of the Federal University of Amapá (UNIFAP) This is a cross-sectional study with a quantitative approach. The data collection instruments were: Beck Depression Inventory (BDI), the Dundee Ready Education Environment Measurement (DREEM) and a sociodemographic questionnaire. The sample consists of students from the second to sixth grade of the medical course at UNIFAP. For the data analysis we applied the chi-square test using SPSS 2.3 statistical software. One hundred fifty-one students responded completely to the questionnaires, constituting a sample of 80% of the study population. Among these, 69 (45.7%) had some degree of depression: 32 (21.2%) students had mild to moderate characteristics, 27 (17.8%) had moderate to severe depression and 10(6.6%), severe depressive symptoms. The score reached in the BDI was higher in academic who had desire to change course, difficulty in social relationships and those who assessed the school environment as having many problems. It was concluded that the prevalence of depressive symptoms in medical students of UNIFAP was higher than that found in the general population and similar to those found in medical students from other institutions. The desire to change course, social relationships and the perception of the learning environment were the variables related to the occurrence of depressive symptoms.
Keywords: Estudantes de medicina - Depressão; Estudantes de medicina - UNIFAP; Estudantes de medicina - Saúde mental; Estudantes de medicina - Transtornos psiquiátricos; CNPQ::CIENCIAS DA SAUDE